Investigating the Impact of Sustainable Development Supply Chain on Economic Performance: An Empirical Study of Sultanate of Oman - Faris Nasif Alshubiri; Muawya Ahmed Hussein (International Journal of Supply Chain Management, 2016)
Abstract---This study aims toinvestigating the impact of sustainable development supply chain on economic performance ofSultanate of Oman. This study used nine sectors in the market classified at three elements of sustainabledevelopment supply chain consists of social , economic and environmental, each element measured by three variablesas independent variables to show the impact on economic performance measured by GDP and FDI on ninegovernorates of Sultanate of Oman over the period 2005 -2013.The statistical descriptive results showAl-Batinah,Dhofar and Muscat governorates have first rankin social element variables.In economic and environmental elements variables Al-Batinah and Muscat governorates have first rank. But AlWusta governorate has the last rank in all three elements of sustainable development supply chain. The regression analysis results show thatsocial sustainable development supply chain variables are more significant in GDP than FDI variables, but in economic sustainable development supply chain variables are only significant in FDI variable .Finally, in environmental sustainable development supply chain variables is more significant in FDI than GDP variablesat 1%, 5% and 10% significant level. Multiple regression analysis testsfound there is as significant impact only in environmental sustainable development supply chain variables on FDI variable.The researchers recommend the need to limit domestic spending and enhance the contribution of small and medium-sized firms in the development and strengthening local value added.